SYNTHESIS OF POTENT ANTAGONISTS FOR THE NATRIURETIC PEPTIDE CLEARANCE RECEPTOR - Ratemi, Elaref (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The objective of this research was to design and prepare natriuretic peptide clearance receptor (NPR-C) clearance receptor antagonists with potential therapy for achondroplasia, an autosomal dominant disorder that interferes with the synthesis of the cartilage growth plate of long bones. Methods: Peptides were synthesized by the standard solid-phase peptide synthesis (SPPS) protocol on Rink resin using the N-Fmoc/t-butyl protection methodology. Biological activity of NPR-C antagonists was assessed using ATDC5 cells. Results: SPPS rapidly generated many crude compounds with purities exceeding 80%. The synthesized ligands were further purified by liquid chromatography-mass spectrometry (LC-MS), and their identities were confirmed by MS and nuclear magnetic resonance. Ligands with nanomolar potencies were obtained. Conclusion: Structure-activity relationship studies resulted in a good selection of stable, low nanomolar, and linear NPR-C antagonists.